Radical-mediated aerobic oxidation of substituted styrenes and stilbenes. (25th October 2021) - Aman, Hasil; Chiu, Wei-Hua; Liu, Pin-Heng; Chuang, Gary Jing
Abstract : A 2, 2-azobis(isobutyronitrile)-catalyzed oxidative cleavage of alkenes with molecular oxygen as the oxidant was described. Abstract : A 2, 2-azobis(isobutyronitrile)-catalyzed oxidative cleavage of alkenes with molecular oxygen as the oxidant was described. Carbonyl compounds and oxiranes were obtained in moderate yield under mild conditions. This study provided useful insights into the mechanism of aerobic oxidative cleavage of alkenes.